Diseño de un manual de control interno para inventarios basado en el informe COSO I en el Comercial “Ventascorp S.A.” del Cantón Quevedo periodo 2021. - Cevallos Guamán, Jessica Samantha (2021)
Internal control is a very useful tool to evaluate and improve the performance of the functions of any business, company, on the other hand inventories is the set of goods or items that the company has for marketing, so it was proposed as an objective to design a manual of functions, policies and procedures for the area of inventories in the "Comercial Ventascorp S. A" in Quevedo canton because its business line depends on the efficiency and effectiveness of inventories for the development of this research information was obtained through the use of research techniques such as observation, interview with the general manager of which the respective SWOT analysis was performed to identify what is the current situation of the commercial and recognize its internal and external analysis in the same way the internal control questionnaire COSO I was applied from which it was identified that the commercial has some shortcomings in the area of inventories.